A marriage between hard and soft approaches against sea level rise and floods within Sg Sarawak - Alexander Kiew, Sayok; Mah, D.Y.S.; Lee, Guan Heng (2015)
The paper is stemmed from the projection of sea level rise for Sg Sarawak Basin. Excessive flooding is forecasted in the coastal region and estuary of Sg Sarawak. Suggestions on how to deal with the sea level rise and flooding in the river basin are discussed based on geographic locations. The concept of Ecosystem-Based Adaptation is taken as the main priority in choosing the appropriate mitigation strategies. At the end of this paper, a summary of proposed hard and soft measures are tabulated and justified.